Transferability of Various Molecular Property Tensors in Vibrational Spectroscopy - Yamamoto, Shigeki; Li, Xiaojun; Ruud, Kenneth; Bouř, Petr (Journal of chemical theory and computation, 2012)
Transfers of polarizability, dipole, and energy derivatives from smaller fragments enable extension of ab initio vibrational spectral simulations to larger molecules. The accuracy of the transfer, however, varies according to the molecule and the tensor type. Recent works (J. Chem. Theory Comput.2011, 7, 1867 and Coll. Czech. Chem. Commun.2011, 76, 567) questioned the accuracy of the tensor transfer for Raman optical activity (ROA) spectra. To estimate relative errors, the current study systematically compares transfer properties for four spectral types (ROA, Raman, vibrational circular dichroism (VCD), and infrared absorption (IR)). As test molecules, polyglycine and polyproline peptides in polyproline II and α-helical conformations were used. The results indicate that the discrepancies could be caused by variation of the transfer parameters but not by fundamental differences in the ROA tensor properties. In particular, when done consistently, the transferred electric and magnetic dipole derivatives, polarizability tensors, and harmonic force field provided a reasonable convergence of all spectra for transfers with increasing sizes of the fragments. The polarized spectroscopies (VCD and ROA), however, were found to be significantly more sensitive than the unpolarized (IR, Raman) ones. Optimization of the geometry and the character of the amino acid side chain was relatively unimportant for the transfer. On the other hand, intramolecular hydrogen bonds in the helix required larger fragments for the same accuracy than in an unfolded peptide. Nevertheless, with reasonable fragmentation, all the spectra (IR, VCD, Raman, and ROA) of the target structures could be reconstructed to an accuracy sufficient for a full interpretation of the experiment, with substantial savings of computer time as an added benefit.